Cultural Incorporation into Graphic Design Learning in South Africa: Learners’ Voices - Blose, Princess; Adekola, Ayobami Precious (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
The incorporation of cultural traditions into education is gaining recognition worldwide. In South Africa, the Curriculum and Assessment Policy Statement for the subject of Technology encourages learners to explore the intersection of societal values, technology, community, and the natural world. This study investigated the impact of cultural traditions on the acquisition of graphic design skills among senior-level technology learners, guided by the social learning theory. We examined how cultural norms influenced graphic design education, focusing on a group of Grade 9 learners in the Mgwenya circuit in Mpumalanga Province, South Africa. The data were collected through qualitative semi-structured interviews and classroom observations. The analysis was conducted using the interpretative phenomenological analysis framework. The study found that while learners understood the subject content, they lacked awareness of graphic design methodologies and did not effectively incorporate cultural elements into their work. This was attributed to the absence of supportive environments, opportunities for cultural expression, and genuine appreciation for cultural diversity. This study highlights the vital role of cultural practices in graphic design education within the Technology curriculum, emphasizing the need for a more inclusive and culturally responsive approach.